Identity of 4a-carbinolamine dehydratase, a component of the phenylalanine hydroxylation system, and DCoH, a transregulator of homeodomain proteins. - Citron, B A (1992)
The principal pathway for the metabolism of phenylalanine in mammals is via conversion to tyrosine in a tetrahydrobiopterin-dependent hydroxylation reaction occurring predominantly in the liver. Recently, the proposal that certain hyperphenylalaninemic children may have a deficiency of carbinolamine dehydratase, a component of the phenylalanine hydroxylation system, has widened the interest in this area of metabolism. Upon cloning and sequencing the dehydratase, we discovered that this protein is identical to DCoH, the cofactor which regulates the dimerization of hepatic nuclear factor 1 alpha, a homeodomain transcription factor. The identity of the nuclear and cytoplasmic proteins is demonstrated by size, immunoblotting, stimulation of phenylalanine hydroxylase, and dehydratase activity. The evolution of the dual functions of regulation of phenylalanine hydroxylation activity and transcription activation in a single polypeptide is unprecedented.